Tubercular posterior scleritis: A case report and review of literature - Aanchal Mehta Agarwal; Parthopratim Dutta Majumder (Indian Journal of Ophthalmology, 2019)
A 47-year-old female presented with optic disc oedema, peripapillary subretinal fluid and scattered areas of choroiditis. Her ultrasound B-scan showed sclerochoroidal thickening with widening of sub-Tenon space. Subsequent investigations revealed a positive Mantoux test and high-resolution computed tomography of the chest was suggestive of pulmonary involvement. She responded well to antitubercular treatment and systemic corticosteroid. A review of the literature was conducted to identify additional reports on similar cases and discussed. A high index of suspicion and appropriate laboratory work-up can aid in the diagnosis of tuberculous posterior scleritis.